The Millennial Generational Style: New Global Political and Economic Orientations - Neslihan Kevser Çevik (Journal of Economy Culture and Society)
In this paper, using Mannheim, I identify Millennials (covering both Gen Y and Gen Z) as a global generation that has spawned a new generational style. I provide a brief overview of the historical conditions that have shaped Millennials’ life experiences. In a nutshell, Millennials have come of age in a new world marked by an ongoing shift in actorhood from macro structures to micro agents. I argue that this formative experience has impelled at least three meaningful norms that distinguish Millennials’ generational style: self-reliance, quotidianism and regeneration. I then trace manifestations of these norms in politics and the economy. I suggest that in politics, the push for self-reliance takes the form of a self-responsible citizen, quotidianism is manifested through a shift towards politics of the ordinary, and regeneration is embodied in Do-it-Yourself (DIY) politics. In economics , on the other hand, the self-reliant actorhood is reflected through the new occupational profile of the ‘maker’, quotidianism is expressed through non-traditional types of work monetizing individuality and personality, and finally regeneration takes the form of critical making. I conclude with implications for social theory on youth and change. The paper attempts to move beyond the dichotomous view of youth either as threats or as heroic figures and propose a broader conceptualization of young adult’s agency to capture how ordinary youth create new centers of configuration in society, from new citizenship norms to new market patterns.